FINANCIAL RISKS AND FINANCIAL DERIVATIVES - URBANIKOVA, Marta (Trends in education, 2008)
The aim of the article is to present the financial risks which are related to the present development on the financial markets and show the posibilities of their elimination by using financial derivatives.
Keywords: financial risks; financial derivatives; forwards